When context modulates the influence of action observation on language processing - Beauprez, Sophie-Anne (PLoS One, 2018)
Numerous studies in the field of embodied cognition have shown a crosstalk between language and sensorimotor processes. In particular, it has been demonstrated that perceiving an action influences subsequent language processing. However, when studying the effect of action observation on language processing it has not been considered whether the context of action presentation could modulate this influence. To test this assumption, the participants in our study observed a prime, specifically a cartoon picture of a person performing an action in either a usual or an unusual context, and then had to perform a semantic decision task involving action verbs that could be congruent or incongruent with the action in the prime. Data analyses showed a significant difference on response times for congruent action verbs compared with incongruent action verbs in the usual context, whereas no difference was observed in the unusual context. This finding indicates that the influence of action observation on language appears only with usual actions, suggesting that the context of action presentation is crucial to enable the influence of action observation on action verbs processing.